Hypokalemic Periodic Paralysis: A case Report and Review of the Literature - Awadelkareem, Ahmed; Habiballah, Motwakil Adam; SalihYousif, Ashgan; Ahmed, Khalil Gamal (Gezira Journal of Health Sciences, 2017)
Hypokalemic periodic paralysis (hypoPP) is a disorder that causes occasional episodes of muscle weakness and sometimes a lower than normal level of potassium in the blood during the attack. HypoPP is one of a group of genetic disorders that includes hyperkalemic periodic paralysis and thyrotoxic periodic paralysis among others. A 45 year old male presented with quadriplegia for 1 day of sudden onset following heavy exercise one day before the attack, Laboratory evaluation revealed a markedly low potassium level of 1.7 meq/L, normal thyroid function test , and normal magnesium level . The patient's paralysis resolved during replacement of his low potassium within 48 hours of ICU admission and he was discharged with no neurologic deficits. He has a family history of similar condition (1 st and 2 nd degree relatives).